The Perceptions of ICU Nurses in Delivering Culturally Sensitive Care at the End-of-Life in the Adult Intensive Care Unit: An Interpretive Description Study - Wachmann, Kristine (My University, 2023)
Background: Death is a common occurrence in the Intensive Care Unit (ICU), and the circumstances surrounding a patient’s death can have a lasting influence on the wellbeing of families and nursing staff alike. Culture is an important influence on an individual’s perspective of end-of-life (EOL) care and a ‘good death’, and, as such, cultural sensitivity is an essential element of high quality EOL care in the ICU. Nurses are well situated to facilitate culturally sensitive EOL care within the ICU; however, there is a significant paucity of knowledge regarding ICU nurses’ perceptions of a culturally sensitive EOL nursing practice and their experiences delivering this within an adult ICU. Aims: The purpose of this study was to explore ICU nurses’ perceptions of delivering culturally sensitive care within their current EOL practice, and thus better understand how culturally sensitive EOL care can be supported within adult ICUs. Design and Methods: An Interpretive Description methodology was utilized to explore the perceptions of seven (n=7) Canadian ICU nurses regarding culturally sensitive EOL care. Maximum variation and theoretical sampling were used to recruit registered nurses from ICUs in two hospitals in Southern Ontario, Canada. Data were generated using semi-structured interviews and field notes and was concurrently analyzed using a constant comparative and reflexive approach. Study rigour was supported through the use of reflexive journaling/memoing, data triangulation, and peer debriefing. Results: Analysis of the data led to the construction of three themes which described nurses’ perceptions of providing EOL care within the ICU: 1) culturally sensitive EOL care is truly person-centered care, 2) dissonance between culturally sensitive EOL care and the biomedical model of care in the ICU, and 3) needing support to adopt a more relational approach to care in the ICU. Conclusion and Implications: Study findings highlight that ICU nurses perceive that culturally sensitive EOL care primarily involves building a strong therapeutic relationship and being truly person-centered when delivering care. However, the context surrounding nursing practice in the ICU creates many barriers to adopting this relational approach to care; thus, multifaceted support is needed for culturally sensitive EOL nursing practice to be bolstered and sustained.
Keywords: Cultural Sensitivity; End-of-Life Care; Intensive Care; Nursing; Critical Care